Efektivitas Terapi Relaksasi Progresi Terhadap Penurunan Kadar Gula Darah Pasien Diabetes Melitus Tipe 2 di Rumah Sakit Estomihi - Anjelika Laoli; Mhd. Taufik Daniel Hasibuan (PT. Hasba Edukasi Mandiri, 2025)
For diabetes mellitus sufferers, progressive relaxation therapy techniques are actions that can reduce blood sugar levels and muscle tension in the body. This can happen because of the pressure process to release hormones in the body. In diabetes mellitus patients, positive coping mechanisms can reduce blood sugar levels so that they can maintain a good quality of life. This progressive therapy is an alternative method of increasing muscle strength, sleep quality for the elderly, reducing blood sugar levels, so that progressive relaxation can be successfully used as a supportive therapy for treating dysfunctional patients. Objective: To determine the effectiveness of Progressive Relaxation Therapy in reducing blood sugar levels in Type II Diabetes Mellitus patients. Method: quantitative method with experimental research design with quasy experimental method with one group pre-test and post-test approach design. The sampling technique uses total sampling. Results: The results of this study show that there is an effect of the effectiveness of progressive relaxation therapy on reducing blood sugar levels in type II diabetes mellitus patients at Etomihi Medan Hospital with a value of p = .001 or p <0.005. Conclusion: Based on research conducted, there is a significant effect of progressive relaxation therapy on reducing blood sugar levels in type II diabetes mellitus patients at Estomihi Medan Hospital.